Management Of Chronic Diseases: Best Practices In Handling Conditions Like Diabetes Or Hypertension (The Review of Diabetic Studies, 2024)
Background: Worldwide, diabetes and hypertension rank among the top chronic diseases in terms of both morbidity and mortality. To avoid complications like cardiovascular disease, kidney damage, or stroke, these problems necessitate long-term care, changes to one's way of life, and strict adherence to treatment regimens. As educators, care coordinators, and advocates for their patients, nurses are essential in the management of various illnesses.Aim: Prevention of problems, improvement of quality of life, and reduction of the load on healthcare systems are the goals of chronic illness management, including diabetes and hypertension.Conclusion: Prevention, patient education, and personalized treatment regimens are the lynchpins of an interdisciplinary approach to the successful management of chronic diseases like hypertension and diabetes. In their function as primary caregivers, nurses are vital in keeping tabs on patients, recommending healthy lifestyle modifications, and building a rapport with them so that they may work together to improve their health. A better quality of life and more control over one's health can be achieved when best practices like telemonitoring, frequent monitoring, encouraging physical activity, and good eating are implemented. In order to alleviate the strain that chronic diseases place on both individuals and healthcare systems, it is crucial to adopt a comprehensive and patient-focused strategy.